2016
DOI: 10.3390/ijerph13080801
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Combined Obesity Indices to Predict Cardiovascular Diseases Risk Factors and Metabolic Syndrome in Northeast China

Abstract: Background: Obesity is associated with cardiovascular disease (CVD) risk factors (hypertension, dyslipidemia and diabetes) and metabolic syndrome (MetS), and it may be flawed that most studies only use one obesity index to predict these risk factors. Therefore, our study aims to compare the various combined obesity indices systematically, and to find the optimal combined obesity indices to predict CVD risk factors and MetS. Methods: A total of 16,766 participants aged 18–79 years old were recruited in Jilin Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
2
6
1
3
Order By: Relevance
“…It has been reported that central obesity is one of the main characteristics of MetS, particularly due to increased values of free fatty acids in the blood and the inhibition of insulin action in peripheral tissues [50,51,52]. In the present study, we observed 10.7% of central obesity in the population assessed, a value that increased to 56.6% in individuals with MetS.…”
Section: Discussionsupporting
confidence: 61%
“…It has been reported that central obesity is one of the main characteristics of MetS, particularly due to increased values of free fatty acids in the blood and the inhibition of insulin action in peripheral tissues [50,51,52]. In the present study, we observed 10.7% of central obesity in the population assessed, a value that increased to 56.6% in individuals with MetS.…”
Section: Discussionsupporting
confidence: 61%
“…However, BMI cannot distinguish between lean mass and fat mass, and WC cannot account for the influence of height on risk 13 . It was supported that BMI and WC were the optimal combinations for Chinese people to predict CVD risk factors and metabolic syndrome 14 .…”
Section: Introductionmentioning
confidence: 92%
“…As reported by the American Diabetes Association criteria, subjects with one of the following components were diagnosed of T2DM: (1) fasting plasma glucose ≥126 mg/dL (2) hemoglobin A1c test ≥6.5% (3) random plasma glucose ≥200 mg/dL (4) past history of diabetes status, or use of antidiabetic agents 41 .…”
Section: Methodsmentioning
confidence: 99%